Working With Me: Revisiting the Tutorial as Academic Care - Engward, Hilary; Goldspink, Sally (Frontiers in Education, 2020)
Tutoring in one form or another is a consistent feature in the higher education learning experience. However, the tutorial relationship involves an intricate mix of intra and interpersonal dynamics which influence short and long-term learning. In this paper, work from a phenomenological study of distance learning students provides transferable insights about the immediate and lasting impact of the tutorial relationship. Ideas from Heideggarian hermeneutic phenomenology are translated to the context of contemporary higher education to establish how achieving a sense of being-with has affective implications to help students to strengthen resilience and the capacity to challenge, confirm and develop confidence in their new learning, thinking and actions. The discussion introduces and unravels the nature of academic care in relation to working with learner vulnerability to enhance ability. Re-conceptualising the tutorial as a form of academic care can provide support and security for learners at a time of unsettlement without lessening their autonomy. We argue that by creating an atmosphere of academic care, learners are empowered and inspired to be courageous and curious, both in the immediate and longer-term. The discussion refocuses the tutorial relationship through ideas and applied strategies for successful future-facing tutoring practices, without major upheaval to the existing operational tutoring infrastructure within the HEI.